ANALISIS VIRTUAL REALITY PADA GAME BOXING DI GAME BLINK KOTA PADANG - Ilham Saputra; M. Syifa Al Farisi, Muhammad Ihsan, Nadya, Achmad Roid Al Gazani, Aulia Janatun Nissa, Wilda Turahma (ADISAM PUBLISHER, 2024)
Virtual Reality (VR) has changed the paradigm in the world of gaming by providing deep and immersive experiences, especially in the context of sports such as boxing. The Blink game in Padang City is an innovation that uses VR technology to provide users with a realistic experience in boxing simulations. This research aims to investigate the implementation and impact of using VR in the Blink Game. The research method used is a qualitative approach with a focus on in-depth analysis of user experience, integration of VR technology, and its social and economic implications. This study revealed that the use of VR in the Blink Game succeeded in increasing the user's level of immersion and interaction with the boxing simulation environment. The realistic experience oflered by VR allows users to experience the physical sensations of boxing in a more immersive way, thereby enriching their gaming experience. Apart from that, the integration of VR technology in Game Blink also raises the potential for collaboration between the gaming industry and boxing athletes in developing boxing techniques and strategies. However, this research also identified several challenges that need to be overcome regarding the implementation of VR in the context of sports gaming. These challenges include the problem of high costs in developing and maintaining VR technology, as well as the uneven expansion of accessibility for users. Nonetheless, VR in Game Blink shows great potential in changing the way we interact with the sport of boxing and makes a significant contribution to the future development of the gaming and sports industry